2011
DOI: 10.1128/aac.00833-10
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Spectrum of Activity of Finafloxacin, a Novel, pH-Activated Fluoroquinolone, under Standard and Acidic Conditions

Abstract: Finafloxacin is a novel fluoroquinolone that exhibits enhanced antibacterial activity under acidic conditions. The aim of this study was to define the in vitro pH-activity relationship. Finafloxacin exhibited optimal antibacterial activity between pH 5.0 and 6.0 at which MICs were 4-to 8-fold lower than those determined at neutral pH. These observations were then confirmed against a larger collection of bacteria. These data suggest that finafloxacin could potentially offer a therapeutic advantage within acidic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 9 publications
2
47
0
3
Order By: Relevance
“…Finafloxacin shares a number of properties, e.g. broad spectrum of activity [1], rapid bactericidal action [2] and a low propensity to select for resistant variants [3], with currently marketed members of the fluoroquinolone class. However, a considerable divergence of antibacterial and pharmacodynamic properties exists amongst these different fluoroquinolones.…”
Section: Introductionmentioning
confidence: 99%
“…Finafloxacin shares a number of properties, e.g. broad spectrum of activity [1], rapid bactericidal action [2] and a low propensity to select for resistant variants [3], with currently marketed members of the fluoroquinolone class. However, a considerable divergence of antibacterial and pharmacodynamic properties exists amongst these different fluoroquinolones.…”
Section: Introductionmentioning
confidence: 99%
“…Finafloxacin has an advantage over other fluoroquinolones in terms of efficacy, especially for the acidic foci of infection (13,15), and has shown minimal toxicity issues during preclinical and clinical trials (15,16). Given that background, the present investigators assumed that finafloxacin might have better activity than conventional fluoroquinolones for treatment of H. pylori infections.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, the efficacy of common fluoroquinolones is weakened in an acidic environment, but the efficacy of finafloxacin is not weakened under those conditions (13,14). The spectrum of in vitro activity and the antimicrobial efficacy of finafloxacin in many other microorganisms were demonstrated previously (13)(14)(15)(16). In addition, many studies have shown considerable finafloxacin antimicrobial efficacy under slightly acidic conditions, such as pH 5.0 (14,16).…”
mentioning
confidence: 99%
“…This constitutes an advantage for the treatment of infections localized in an acidic environment like the urinary and genital tracts, the gastric mucosa, the airways of patients suffering from chronic inflammatory diseases, or abscesses (99) as well as against intracellular infections with phagolysosomal bacteria like S. aureus (98). Finafloxacin MICs against ciprofloxacin-susceptible or resistant Gram-negative bacteria are similar to those of ciprofloxacin at neutral pH but 3-5 dilutions lower at pH 5.2 (99)(100)(101)(102). It is, however, less active than ciprofloxacin on Pseudomonas aeruginosa or other ESKAPE pathogens like Klebsiella or Enterobacter spp.…”
Section: Quinolonesmentioning
confidence: 99%
“…It is, however, less active than ciprofloxacin on Pseudomonas aeruginosa or other ESKAPE pathogens like Klebsiella or Enterobacter spp. (101). In contrast to ciprofloxacin, finafloxacin is not a substrate for the fluoroquinolone efflux system by QepA1 of Escherichia coli (possibly related to its lower hydrophilicity) and is not affected the AAC(6')-Ib-cr acetylase, as it does not display the piperazine ring substrate for this enzyme in position 7 (100).…”
Section: Quinolonesmentioning
confidence: 99%